Attempting to break the chain: reimaging inclusive pedagogy and decolonising the curriculum within the academy. Issue 3 (23rd February 2021) - Arday, Jason; Zoe Belluigi, Dina; Thomas, Dave
Abstract: Anti-racist education within the Academy holds the potential to truly reflect the cultural hybridity of our diverse, multi-cultural society through the canons of knowledge that educators celebrate, proffer and embody. The centrality of Whiteness as an instrument of power and privilege ensures that particular types of knowledge continue to remain omitted from our curriculums. The monopoly and proliferation of dominant White European canons does comprise much of our existing curriculum; consequently, this does impact on aspects of engagement, inclusivity and belonging particularly for Black, Asian and Minority Ethnic (BAME) learners. This paper explores the impact of a dominant Eurocentric curriculum and the Decolonising the Curriculum agenda within higher education and its influence upon navigating factors such as BAME attainment, engagement and belonging within the Academy. This paper draws on a Critical Race Theory (CRT) theoretical framework to centralize the marginalized voices of fifteen BAME students and three academics of colour regarding this phenomena. Aspects examined consider the impact of a narrow and restrictive curriculum on BAME students and staff and how the omission of diverse histories and multi-cultural knowledge canons facilitates marginalization and discriminatory cultures.